Glycemic Control Patterns and Kidney Disease Progression among Primary Care Patients with Diabetes Mellitus - Cummings, Doyle M.; Larsen, Lars C.; Doherty, Lisa; Lea, C. Suzanne; Holbert, Donald (My University, 2011)
Background: Reducing glycosylated hemoglobin (HbA1c) to near or less than 7% in patients with diabetes is associated with diminished microvascular complications, but this level is not consistently achieved. The purpose of this study was to examine the relationship between fluctuations in HbA1c and changes in estimated glomerular filtration rate (eGFR) and estimated stage of chronic kidney disease (CKD) in an academic primary care practice. Methods: We analyzed data from 791 diabetic primary care patients (25% white; 75% African American) enrolled between 1998 to 2002 and followed through 2008 (mean follow-up, 7.6 1.9 years). We calculated baseline and final follow-up eGFR using the Modification of Diet in Renal Disease equation. We examined the relationship between fluctuations in HbA1c and changes in eGFR and stage of CKD using multivariable linear and logistic regression models that controlled for demographic and clinical variables associated with CKD progression. Results: From baseline to follow-up, mean eGFR in African Americans declined to a greater extent and more rapidly than in whites. Age, mean systolic blood pressure, initial HbA1c, initial eGFR, and number of HbA1c values (all P < .01) were significant predictors of change in eGFR. Among HbA1c fluctuation measures, the strongest predictor of change in eGFR was the proportion of HbA1c values >7% (P < .02); however, this contributed little to explaining model variance. Conclusion: These data suggest that traditional demographic and clinical risk factors remain significantly associated with changes in eGFR and that the pattern of variability in HbA1c is only modestly important in contributing to changes in eGFR among African-American and white diabetic patients in primary care.
Keywords: Diabetes; Glycemic control; Kidney disorders